A systematic analysis of bone marrow cells by flow cytometry defines a specific phenotypic profile beyond GPI deficiency in paroxysmal nocturnal hemoglobinuria1. Issue 2 (26th December 2012) - Mannelli, Francesco; Bencini, Sara; Peruzzi, Benedetta; Cutini, Ilaria; Sanna, Alessandro; Benelli, Matteo; Magi, Alberto; Gianfaldoni, Giacomo; Rotunno, Giada; Carrai, Valentina; Gelli, Anna Maria Grazia; Valle, Veronica; et al.
Abstract: Background: Paroxysmal nocturnal hemoglobinuria (PNH) is a unique disorder caused by a PIG‐A gene mutation in a stem cell clone. Its clinical picture can sometimes make challenging the distinction from other disorders, and especially from myelodysplastic syndromes (MDS), since both diseases correlate with cytopenias and morphological abnormalities of bone marrow (BM) cells. Recently, flow cytometry (FC) has been proposed to integrate the morphologic assessment of BM dysplasia, and thus to improve the diagnostics of MDS. Methods: In the present study, we have analyzed systematically FC data resulting from the study of BM cells from patients with PNH and MDS. Results: Our data demonstrated abnormalities in PNH beyond the deficiency of glycosylphosphatidylinositol‐linked proteins and the application of a systematic approach allowed us to separate effectively MDS and PNH in a cluster analysis and to highlight disease‐specific abnormalities. Indeed, the parallel evaluation of some key parameters, i.e. patterns of expression of CD45 and CD10, provided information with practical diagnostic usefulness in the distinction between PNH and MDS. Moreover, the hypo‐expression of CD36 that we observed on monocytes might be related to the thrombotic tendency in PNH. Conclusions: We investigated systematically the phenotypic profile of BM cells from patients with PNH; our data provide useful antigenic patterns to solve between PNH and MDS, sometimes morphologically overlapping. Moreover, some PNH‐related phenotypic changes might be involved in the physiopathology of the disease and further studies addressing this issue are warranted. © 2013 International Clinical Cytometry Society